Loneliness Examined From The Perspective of Self-Esteem and Religiosity in Self-Harm Perpetrators - Annisa Sya'baniatus Silvia; Rr Dwi Astuti (STAI Syaichona Moh. Cholil Bangkalan, 2025)
The increase in cases of self-harm in Indonesia necessitates preventive measures from both the health and education sectors. One such measure is to conduct research on this issue. This study aims to explore the relationship between self-esteem, religiosity, and loneliness among self-harmers. A total of 368 participants were involved in this study, namely self-harmers aged 16 to 38 years old in Indonesia, who were selected as the population using a purposive sampling approach.. Data were collected using loneliness, self-esteem, and religiosity scales adapted into Indonesian. Data analysis using a two-predictor regression test found that the significance value of the p-value was 0.000 (p < 0.01), and the value of Rx1,2y = 0.611 was obtained. The R-squared value of 0.373 indicates that the study contributes an effective 37.3%, thereby confirming that the hypothesis stating there is a significant negative relationship between self-esteem and religiosity with loneliness among self-harm perpetrators is acceptable. This means that the higher the religiosity and self-esteem of an individual, the lower the level of loneliness experienced by self-harmers.